$ over ethics: higher education and the private prions industry, a symptom of the theology of neoliberalism - Rothe, Dawn (Critical criminology, 2022)
Neoliberalism’s impact on our everyday lives, culture, and institutions is powerful and ubiquitous. One might suspect that higher education, especially non-profit colleges and universities, would be less affected and more resistant to the expansion of market-driven logic and the hyper-capitalist ethos of neoliberalism, but much evidence points to college and university subscription to the tenants of this ideology and practice. This is especially the case as state policy leaders, particularly conservative and neoconservative Republicans, are aggressively disinvesting in higher education, reducing or removing completely governmental responsibility to ensure an educated population in favor of market-driven forces. While we provide a brief overview of the corporatized universities of today and its problematic nature, we focus on the impact of corporate donations on universities, with particular attention to the private prison industry’s intertwinement with higher education, and specifically the relationship between the GEO Group and Florida Atlantic University.